2015
DOI: 10.1071/ch14400
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Thermal Stability of New Polynitrostilbenes

Abstract: New polynitrostilbenes were directly synthesised by the Knoevenagel condensation of aromatic aldehydes with nitrotoluenes. The differential scanning calorimetry results demonstrated that the introduction of an amino group and C=C double bonds could improve the thermal stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The highest probability of an EM to be thermostable was found in explosives having HBP in the relatively narrow range 50–70%. The latter group of explosives includes single-ring compounds, such as A4 (TATB), A15 (ANPZ), A13 (DADNPO), and A14 (LLM105), as well as some bridged EMs, such as D5 (TKX55), E9 , D7 , and D9 …”
Section: Dft Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest probability of an EM to be thermostable was found in explosives having HBP in the relatively narrow range 50–70%. The latter group of explosives includes single-ring compounds, such as A4 (TATB), A15 (ANPZ), A13 (DADNPO), and A14 (LLM105), as well as some bridged EMs, such as D5 (TKX55), E9 , D7 , and D9 …”
Section: Dft Calculationsmentioning
confidence: 99%
“…The latter group of explosives includes single-ring compounds, such as A4 (TATB), A15 (ANPZ), A13 (DADNPO), and A14 (LLM105), as well as some bridged EMs, such as D5 (TKX55), E9, 47 D7, 41 and D9. 43 Our further analysis of correlation between EMs' HBAs and their thermostability showed that heat-resistant explosives prevalently have HBA values in a range between 90 and 180 Å 2 (Figure 23). Grouping compounds with similar HBA and thermostability properties together, we could draw three different clusters for each of HL3, HL7, and HL9 explosives.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The absorption peaks at around 270 and 370 nm were primarily due to the π–π* transition and the n –π* transition. [ 33 ] All 12 catalysts exhibited strong absorption peaks at 450 nm, which was due to the replacement of hydrogen on the benzene ring by the group containing n electrons on the para position. [ 34 ] It enhanced the conjugation of n –π* and shifted the absorption wavelength to the long‐wave direction.…”
Section: Resultsmentioning
confidence: 99%
“…At the first attempt, we tried to prepare the target catalysts according to a previously reported method, [32,33] but many mixtures were obtained. Then, we optimized the methods of their synthesis such as setting the size of the silica gel to 37-48 μm.…”
Section: Preparation Routementioning
confidence: 99%